Liquid phase assisted high pressure sintering of dense TiC nanoceramics. Issue 15 (15th October 2018) - Liu, Lixin; Wang, Bing; Li, Xuhai; He, Qiang; Xu, Liang; Cao, Xiuxia; Meng, Chuanmin; Zhu, Wenjun; Wang, Yuan
Abstract: To address the difficulty of achieving high density while effectively suppressing grain growth in the fabricating of nanoceramics, this paper demonstrates a novel integrated approach, consisting of a solid-liquid reaction, high pressure and low temperature sintering, to prepare dense nanocrystalline TiC ceramics. Using Si as the additive, a low-viscosity Si liquid phase is formed under the sintering condition of 1200 °C/4.5 GPa. It is shown that both of the sintering aid and high pressure are crucial in achieving high density nanostructured TiC ceramics and controlling their microstructure and thus their mechanical properties. The pure TiC can be sintered to reach 95.3% of its theory density and, with the assistance of liquid Si additive, it can be sintered to full densification without grain growth by high pressure technique.